2012
DOI: 10.1126/science.1218959
|View full text |Cite
|
Sign up to set email alerts
|

Major Earthquakes Occur Regularly on an Isolated Plate Boundary Fault

Abstract: The scarcity of long geological records of major earthquakes, on different types of faults, makes testing hypotheses of regular versus random or clustered earthquake recurrence behavior difficult. We provide a fault-proximal major earthquake record spanning 8000 years on the strike-slip Alpine Fault in New Zealand. Cyclic stratigraphy at Hokuri Creek suggests that the fault ruptured to the surface 24 times, and event ages yield a 0.33 coefficient of variation in recurrence interval. We associate this near-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(199 citation statements)
references
References 30 publications
(7 reference statements)
10
189
0
Order By: Relevance
“…The time-dependent nature of the Loma Blanca earthquakes is consistent with recent work that documents quasiperiodic earthquake recurrence intervals on some plate-boundary faults (14)(15)(16)(17). However, other plate-boundary faults exhibit random or clustered earthquakes over time scales of thousands of years (8)(9)(10)(11)(12)(13).…”
Section: Fluid Infiltrationsupporting
confidence: 73%
See 1 more Smart Citation
“…The time-dependent nature of the Loma Blanca earthquakes is consistent with recent work that documents quasiperiodic earthquake recurrence intervals on some plate-boundary faults (14)(15)(16)(17). However, other plate-boundary faults exhibit random or clustered earthquakes over time scales of thousands of years (8)(9)(10)(11)(12)(13).…”
Section: Fluid Infiltrationsupporting
confidence: 73%
“…This view has led to greater use of "time-independent" and clustered earthquake recurrence models. Although an increasingly large body of research has shown that many seismogenic plate-boundary faults around the world exhibit quasiperiodic failure (14)(15)(16)(17), comparatively slow recurrence rates in conjunction with short paleoseismic records have until now prevented robust assessment of earthquake recurrence intervals for intraplate faults. We address this fundamental knowledge gap by using a significantly different approach; direct dating of coseismic veins preserved as part of the long-term rock record.…”
mentioning
confidence: 99%
“…The largest late Quaternary fault displacement rates in the region occur on the central Alpine Fault (27 AE 5 mm a À1 strikeslip and approximately 10 mm a À1 dip-slip rates -Norris & Cooper 2001; Sutherland et al 2006) along the western side of the alps. Although it has not produced any major earthquakes or measureable creep during New Zealand's < 200 year written history, paleoseismologic evidence suggests this mature transpressive fault ruptures regularly in great (magnitude M~8) earthquakes at recurrence intervals of 329 AE 68 years Berryman et al 2012). The most recent rupture was approximately 1717 AD, so the fault appears to be late in the cycle of stress accumulation that will lead to a future large earthquake (Wells et al 1999;Howarth et al 2012).…”
Section: Setting and Context Tectonicsmentioning
confidence: 99%
“…It may imply the local ambient stress state of the rock mass is important in the evolution of permeability and hydrological responses at intermediate-and far-field distances, so therefore warrants further research. Given also that the Alpine Fault is late in a regular cycle of stress accumulation Berryman et al 2012), some form of rupture seems imminent and much may soon be learnt about the evolution of permeability and the flow regime in the Southern Alps.…”
Section: Key Observations and Interpreted Mechanismmentioning
confidence: 99%
“…This fault-line and the network of others that traverse the country are the foci for major earthquakes (Fig. 3a), with at least 24 major earthquakes (magnitude M w > 7) on the Alpine Fault in the last 8000 years (Berryman et al 2012), including three in the last 600 years (Wells et al 1999). Many earthquakes on smaller fault lines have also caused significant damage to New Zealand forests this century, as evidenced by the November 2016 M w 7.8 Kaikōura earthquake (Hamling et al 2017).…”
Section: New Zealand Forest Disturbance Regimes Geological and Geomormentioning
confidence: 99%